2007
DOI: 10.1309/r1yl4b4bt2wcqdgv
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Cell Counter–Based Parameters and Formulas in Detection of β-Thalassemia Trait in Areas of High Prevalence

Abstract: The present study aimed to retrospectively evaluate the usefulness of cell counter-based parameters and formulas in beta-thalassemia trait (BTT) detection. The study included 170 BTT cases (hemoglobin [Hb]A(2) >4.0% [0.04]) and 30 non-BTT cases (HbA(2), 2.3%-3.5% [0.02-0.04]). Depending on the hemoglobin level and iron deficiency, the BTT group was further classified into classic BTT (n = 112) and BTT with iron deficiency anemia (n = 58). The RBC count, MCH, MCV, RDW, and Shine and Lal, Mentzler, Srivastava, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 8 publications
3
67
1
3
Order By: Relevance
“…Automated measurement of the red cells (RBC) microcytosis and hypochromia has proven clinical usefulness for the differential diagnosis. The present study was undertaken with the main objective of evaluating efficiency of M/H ratios in screening for beta thalassaemia only, which is proved to be a reliable index according to the other studies 10,12,13,[17][18][19][20][21] . Our MH ratio showed similarity to the published indices evaluated by Urrechaga E study, with a Youden index of 76.3% 13,[17][18][19][20][21] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Automated measurement of the red cells (RBC) microcytosis and hypochromia has proven clinical usefulness for the differential diagnosis. The present study was undertaken with the main objective of evaluating efficiency of M/H ratios in screening for beta thalassaemia only, which is proved to be a reliable index according to the other studies 10,12,13,[17][18][19][20][21] . Our MH ratio showed similarity to the published indices evaluated by Urrechaga E study, with a Youden index of 76.3% 13,[17][18][19][20][21] .…”
Section: Resultsmentioning
confidence: 99%
“…There are only few studies reported previously on the M/H ratio [10][11][12] . Moreover, cell counter-based formula has been used in the differential diagnosis of microcytic anemia [10][11][12][13][14][15][16][17][18][19][20] . The reference ranges for these new RBC extended parameters and their values in anaemic patients with red cells abnormalities have been recently established as a good indicator by showing the % microcytosis was more increased in thalassaemia than IDA 5,17 .…”
Section: Discussionmentioning
confidence: 99%
“…[18] South East Asia, [7], [8], [9] India, [5], [6] Mediterranean region [2], [3], [4] and Middle East including Saudi Arabia [2], [3], [4] are the regions from where large number of cases are reported. The change in hematological parameters depends on the type of thalassemia.…”
Section: Heamatological Parametersmentioning
confidence: 99%
“…On the basis of the affected globin chain, the thalassemias are classified into α or β types. The β thalassemia is prevalent throughout the world while α is found more in the Mediterranean region, [1] Middle East, [2], [3], [4] South Asia [5], [6] and South East Asia. [7], [8], [9] The hematological parameters in the thalassemic patients vary with the type and severity of anemia.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies are available in the literature dealing with the dilemma of difficulties in BTT diagnosis during mass screening of population because of the overlapping of cutoff values in BTT and non-BTT subjects. [2][3][4][5][6][7][8][9] Hence we decided to establish the cutoff values in our setup by investigating the parents of children suffering from thalassemia major and receiving blood transfusion in our center who have been confirmed as having BTT.…”
Section: Introductionmentioning
confidence: 99%